Analysis of the quality of life and physical activity level in undergraduate students - doi: 10.4025/reveducfis.v23i2.10924 - Fabricio Cieslak; Jean Fuzetti Cavazza; Leilane Lazarotto; Ana Claudia Kapp Titski; Joice Mara Facco Stefanello; Neiva Leite (Journal of Physical Education (Maringá), 2012)
The study aimed to analyze the quality of life and physical activity level in undergraduate students. Participated in the study 178 undergraduate students (83 males and 95 females). Quality of life was measured by WHOQOL-Bref, and the physical activity level, through the IPAQ. Regarding the quality of life, the male subjects showed higher values for women, however, only with significant differences in the physical domain, psychological domain and overall quality of life. Most participants were classified as active and very active (men=71.1% and women=53.7%), with men showing higher levels of physical activity. The correlations between the quality of life domains and physical activity levels were strong and positive for both genders. We concluded that the domains of quality of life and physical activity level differ between the genders and show positive strong relationships in undergraduate students